DESAIN ALTERNATIF SENI PUBLIK DIBANDARA ADI SUMARMO SURAKARTA - Cholis, Henri (Institut Seni Indoensia Surakarta, 2010)
Adi Sumarmo airport in Surakarta is an international airport located at Boyolali regency which is close to Surakarta city. The aesthetic aspects and elements of the architecture and interior of the airport as an international one should give a strong impression. The character, style and meaning of the aesthetic elements used to beautify the interior and exterior should be adjusted to the vision and mission of Adisumarmo airport, in this case Angasa Pura I. This research was carried out as an effort to discourse on an alternative design of a publick space. Thatâ€™s why, this research studied the aesthetic elements of a public space and it aimed at providing Angkasa Pura I, Adi Sumarmo airport an alternative design of a public space. The other goal was that Adi Sumarmo airport would look more beautiful with the wisdom of local culture. This research is designed as a research studying the creation of a work of public art in a publick space located at Adi Sumarmo airport. The steps of the research are adjusted to the method for creating a work of art such as (1) an observation on the space form into which the work of art would be placed and the library study on public art and culture which would be an icon of Surakarta. (2) the data analysis and validation which would be used as the base or souce of creation, (3) the designing stage which brings out some alternative designs of a work of publick art which later become the aesthetic elements of the airport and a landmark of Surakarta as a city of culture. The result of this research is an alternative design of public art for the interior of Adi Sumarmo airport (Angkasa Pura I) consisting of a mural, reliefs of stone or brass/ bronze, threedimension statue, and a glass painting. The alternative design of public art for the interior of Adi Sumarmo airport (Angkasa Pura I) is adjusted to the image of the airport, the vision and mission of the airport as well as the aesthetic elements taken from the local culture, Javanese culture. Keywords: public art, publick space, Adi Sumarmo airport, cultural identityÂ